Ewing's sarcoma of the sternum necessitating complex resection and reconstruction. Issue 1 (1st January 2019) - Vissers, Gino; Van Houtven, Lucas; Corthouts, Jérôme; Snoeckx, Annemie; Luijks, Marloes; Thiessen, Filip; Tondu, Thierry; Van Schil, Paul
Abstract: We present a 30-year-old man with a sternal Ewing's sarcoma, who was treated by complex resection of the sternal body and reconstruction by a methyl methacrylate sandwich graft and a pedicled latissimus dorsi flap.